1991
DOI: 10.1097/00006842-199103000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Immunological changes in young and old adults during brief laboratory stress.

Abstract: Few data are available on the response of the human immune system to acute psychological stressors under controlled laboratory conditions. Young female subjects (21-41 years) showed increases in natural killer (NK) cell activity, and in the numbers of circulating CD8 suppressor/cytotoxic T cells, and natural killer lymphocytes following a brief (12 minute) stressful mental arithmetic examination. Older female subjects (65-85 years) failed to show the stress-related increase in NK activity. The psychological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
3
9

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(130 citation statements)
references
References 20 publications
7
111
3
9
Order By: Relevance
“…To best capture mood state during the session, the mean of the two assessments was used. The SSR is a validated multidimensional instrument for measuring acute changes in mood during experimental stress (Naliboff et al, 1991). It consists of 12 semantic differential scales, each of which is a 10 cm line anchored by opposite descriptor words (e.g., calm-stressed).…”
Section: Methodsmentioning
confidence: 99%
“…To best capture mood state during the session, the mean of the two assessments was used. The SSR is a validated multidimensional instrument for measuring acute changes in mood during experimental stress (Naliboff et al, 1991). It consists of 12 semantic differential scales, each of which is a 10 cm line anchored by opposite descriptor words (e.g., calm-stressed).…”
Section: Methodsmentioning
confidence: 99%
“…Negative psychosocial factors and chronic stress interact to negatively affect tumor immunity, whereas psychosocial interventions for stress reduction and improved coping strategies positively impact immunity [407,411,412; reviewed in 413]. In contrast, acute psychological stress increased circulating NK cell numbers and/or NK cell activity [414][415][416], but this effect may be followed by reduction below baseline shortly after stress [416]. Interpersonal difficulties, depression, anxiety and chronic stress reduce the number and function of circulating NK cells [417][418][419][420][421][422][423]; effects associated with elevated cortisol levels [424].…”
Section: Sns and Tumor Growthmentioning
confidence: 99%
“…These effects were abolished under 8-blockade, indicating that effective ,B-blockade was achieved. In the immune system, significant increases were found for the number of NK cells and NK cell activity in the placebo group; these increases M W f any studies have shown that acute mental stress is accompanied by rapid and transient increases in cardiovascular variables like blood pressure and heart rate.1-7 These heart rate responses can be inhibited by prior administration of /3-antagonists, indicating that mental stressors activate the (3-adrenergic system.2-4 It has repeatedly been shown in other studies that acute mental stress also affects parameters of the immune system, [8][9][10][11][12] parallel to the effects on the cardiovascular system. As a result, the number and activity of natural killer (NK) cells in peripheral blood increases significantly.…”
Section: Effects Of P-adrenergic Blockade On Immunologic and Cardiovamentioning
confidence: 99%